Digital Empathy Training for Peer Counselors at MAN Rejang Lebong: Building a Foundation for Religious Moderation Among Muslim Youth in the Digital Age - Dina Hajja Ristianti; Idi Warsah; Afrizal Afrizal; Aprianti Aprianti (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
In the digital age, teenagers face new challenges, such as developing empathy and religious moderation. They often struggle to understand tolerance, diversity, and healthy digital communication. The goal of this community service activity is to help peer counselors at MAN Rejang Lebong develop digital empathy as a foundation for religious moderation.  This program aims to provide hands-on training in digital skills, such as understanding religious principles, embracing diversity, and using technology wisely. Interactive training, digital case simulations, and group reflection are among the strategies employed. The results of the program show that peer counselors were able to raise awareness about the importance of empathy in digital interactions, strengthen their understanding of religious moderation, and learn how to support their peers